The impact of alcohol pricing policies on public health in Hong Kong, China: A modelling study - Carmen S. Ng; Minnie Au; Robyn Ma; June Y.Y. Leung; Jianchao Quan (Elsevier, 2022)
Summary: Background: Contrary to most developed economies, Hong Kong has reduced and eliminated taxes on beer and wine over the last 15 years and observed increasing alcohol consumption. Methods: We applied econometric epidemiological modelling to assess the impact of reverting ad valorem taxation to pre-2008 levels (20% on wine and 40% on beer) on consumption and health outcomes. We used 15 years of industry sales and pricing data (2004-2018) to derive 25 own-price and cross-price elasticity estimates. We applied risk functions from the World Health Organization 2018 Global Status Report to assess the impact on 25 alcohol-attributable conditions. Findings: An estimated 616 deaths (91.3% in men) were attributable to alcohol in 2018. Raising taxes to pre-2008 levels is estimated to reduce consumption of pure alcohol consumption by 8.0%, 15.9%, and 31.1%; and reduce alcohol-attributable deaths by 11.6%, 21.8%, and 40.2% assuming 25%, 50% and 100% pass through rates of taxes to consumers. The largest projected decreases in alcohol-attributable mortality in absolute numbers are alcohol abuse, alcohol dependence, and alcoholic psychoses (wholly alcohol-attributable disorders). The largest absolute number of new alcohol-attributable cases in 2018 were hypertension, alcohol dependence and alcohol abuse; which are estimated to be reduced by 31.3%, 34.2%, and 34.3% respectively by raising taxes to pre-2008 levels. The alcohol-attributable health burden and absolute reductions in health harms are far greater in men. Interpretation: Reversing the 2008 alcohol tax reductions is potentially effective in averting the alcohol-attributable health burden and thus mitigate against the avoidable harms of alcohol-related disease. Funding: Health and Medical Research Fund, Food and Health Bureau of the Hong Kong SAR, China [03170067].